Pendidikan Agama Islam untuk Menumbuhkan Kesadaran Ekonomi dan Kepedulian Sosial pada Anak dan Remaja - Ina Nur Fajariyah; Muhammad Syauqi Mubarok; Hasan Fikri (FKIP UNSULTRA, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping the character of children and adolescents, including fostering economic awareness and social awareness. Economic awareness in children and adolescents is not only related to the ability to manage personal finances but also encompasses an understanding of ethical values, social responsibility, and the principles of justice in Islam. This study uses a literature review approach to analyze previous research addressing the implementation of PAI in instilling economic awareness and social awareness. Literature sources were obtained from scientific journals, academic books, and official publications between 2015 and 2025. The study results indicate that integrating the concepts of zakat, almsgiving, hard work, and honesty into PAI learning can enhance children and adolescents' understanding of the importance of managing resources responsibly and foster empathy for the underprivileged. Furthermore, learning based on social practice activities, such as managing charitable funds in schools and community-based entrepreneurship projects, has proven effective in strengthening productive economic behavior and social awareness. These findings confirm that PAI is not merely spiritual education but also a strategic tool in shaping an economically and socially responsible generation. This study recommends integrating the Islamic Religious Education (PAI) curriculum with financial literacy programs and social activities to optimize character development in children and adolescents.